The Influence of Visual Learning Style and Mathematical Learning Motivation on Geometry Understanding of Class X Students of MAN 2 Palu City - Achmad Nuuryadin; Rafiq Badjeber; Yulia Yulia (Journal of Educational Sciences, 2026)
This study aims to analyze the influence of visual learning styles and mathematical learning motivation on the understanding of geometry material of class X students of MAN 2 Palu City. This study is motivated by the importance of visualization abilities and learning motivation in understanding abstract and spatial geometric concepts. The study uses a quantitative approach with an ex post facto research type. The research sample consisted of 219 students selected using a simple random sampling technique. Data collection was carried out through a visual learning style questionnaire, a mathematical learning motivation questionnaire, and a geometry understanding test. Data analysis used multiple linear regression. The results showed that visual learning styles had a positive and significant effect on geometry understanding with a significance value of 0.001. Mathematical learning motivation also had a positive and significant effect with a significance value of 0.001. Simultaneously, both variables had a significant effect on geometry understanding with an F_count value of 163.484 and a coefficient of determination of 0.602. This study concluded that students' geometry understanding was influenced by their visual abilities and mathematical learning motivation.